IMPLEMENTASI MANAJEMEN STRATEGIS DALAM UPAYA PENINGKATAN MUTU PENDIDIKAN DI PONDOK PESANTREN - Purwanti, Eri; Kusuma, Nurhadi; Sari, Ruly Nadian (STIT Pringsewu, 2018)
The purpose of this study is to know the implementation of strategic management in an effort to improve the quality of education in Pondok Pesantren. This research use descriptive, analytic, qualitative method by using field study (field research) in data collection. From the results of research can be concluded: the implementation of strategic management in an effort to improve the quality of education in Pondok Pesantren, has been done well. Efforts to improve the quality of education in boarding schools increased and directed, because the implementation of strategic management made in boarding school can be implemented and the goal is achieved well.